KOMPOSISI TIGA JENIS BASO DI JAKARTA - Ignatius Tarwotjo; Sri Hartini; S. Soekirman; Sumartono Sumartono (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 1971)
Komposisi tiga djenis baso di Djakarta. (The nutrient composition of three kinds of "baso" (meat ball) in Djakarta). "Baso" (meat ball) is a popular dish in the urban communities. Its significance in the daily consumption pattern can not be neglected. Proximate analysis was carried out on three kinds of "baso" available in Djakarta, namely: "baso sapi" (beef baso) sold in restaurants and also by house-to-house vendor, and "baso ikan" (fish baso). The protein contents were as follows: 10.91% in "baso sapi" sold in restaurants, 5.04% in "baso sapi" sold by the vendor, and 9.21% in "baso ikan". Mengingat banyaknya penjual baso, maka tidak mustahil makanan ini memegang peranan yang tak dapat diabaikan dalam konsumsi zat gizi penduduk, terutama pada masyarakat kota. Ternyata baso belum tercantum dalam Daftar Komposisi Bahan Makanan Indonesia yang ada sampai saat ini.Penyelidikan ini ditujukan untuk melengkapkan data tentang bahan makanan ini, dalam rangka penyempurnaan Daftar Komposisi Bahan Makanan Indonesia.